The Determination of Rational Values of the Parameters of an Unventilated Trombe Wall Using the Method of Multicriteria Optimization for the Climatic Conditions of Uzbekistan - A’zamovich, Samiev Kamoliddin (International Journal of Sustainable Construction Engineering and Technology, 2022)
The energy demands of the construction sector are expected to multiply over the next decade, driven by population growth, rising incomes, accelerating urbanization and changes in consumption patterns. This process is also dramatically affected by the depletion of fossil resources and high specific energy consumption for heating buildings. Under these conditions, it is necessary to develop comprehensive energy efficiency measures in these areas to meet the energy demands of residential, commercial and administrative buildings.In this work, using the methods of degree-day, multicriteria optimization and regression analysis, the optimal combinations of factors for an unventilated Trombe wall are determined: the orientation of the building, the thermal support of the translucent enclosure of the unventilated Trombe wall and the ratio of the surface of the unventilated Trombe wall to the surface of the building facade. The calculations were performed for three levels of thermal protection for buildings in the climatic conditions of the city of Tashkent (Uzbekistan). A typical one-storey three-room house was chosen as the object.As the calculation results show, within the considered range of values, the relative dominances of the factors are as follows: orientation - 5.37%; thermal support of translucent barriers - 72.95%; and area ratio - 21.68%. Using the optimal values, the specific energy consumption of buildings for heating can be reduced from an average of 12.9-14.8% to 52.6-65.3%. Additionally, the CO2 emissions are reduced from 5621.8 kg to 12435.5 kg per year. The discounted payback period, depending on the investment, ranges from 18.7 to 40.9 years. Regression equations are proposed for three levels of thermal protection of the considered object, making it possible to determine the specific energy consumption for heating.